EDUCATION MANAGEMENT PROFESSIONALISM OF ISLAMIC BOARDING SCHOOLS IN INDONESIA - Halim Purnomo (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This study analyzed the organizational commitment and professionalism of leaders, teachers in Islamic boarding schools in Indonesia by observing the leadership style, organizational culture, and intelligence of the manager. This research is quantitative research, with the unit of analysis being the leader and teachers of Islamic boarding schools in Indonesia. Researchers measure organizational culture variables that include eight dimensions: trustworthy, creative thinking, competent, cooperative, development, pride, sanctions and rewards, and communicative. The leadership style has a significant positive effect on organizational commitment, organizational culture has a significant positive effect on the organizational commitment, spiritual intelligence has a significant positive effect on the organizational commitment, the professional managers on Islamic leadership, Islamic organizational culture has a positive and significant effect on the professionality of managers, the professional managers on spiritual intelligence, and organizational commitment has a positive and significant effect on the professionality of managers.